Case series of clinical study and surgical management of atlanto axial dislocation our institute experience - Dasari, Ravi; Prasad, K. Satyavara; Sandeep, B.; Raman, B. V. S. (International Journal of Research in Medical Sciences, 2017)
Background: Atlantoaxial dislocation refers to a loss of stability between the atlas and axis (C1-C2), resulting in loss of normal articulation. Cervical spine C1-C2 motion segment is the most technically challenging. Methods: This is a prospective and retrospective Study which included 34 patients admitted in King George hospital, Andhra medical college, Visakhapatnam over the past two years (January 2014- January 2016) with AAD. Results: The age of the patients ranged from 3 to 60 years with mean age being 37.67 years. Commonest presenting sign is local tenderness at the back of upper cervical region in 91.17%. Most common procedure done was single sitting trans oral odontoid decompression with posterior occipito cervical fusion with occipital plate and C2, C4 polyaxial screws and lateral mass rods in 18 cases out of 34. The next common procedure performed was C1 lateral mass and C2 pars screw fixation 8 out of 34. Conclusions: Trans oral odentoidectomy and posterior ocipito cervical fusion is ideal and still holds good for irreducible AAD with ventral compressive pathology.